Radiation effect of wireless fidelity (wi-fi) on oocyte number of oocyte stimulation in mice (mus musculus) - Nurbayatin, Anita; Widjiati, Widjiati; Primariawan, Relly Yanuari; Poernomo, Bambang; Sulistiawati, Sulistiawati; Yudiwati, Rina (Folia Medica Indonesiana, 2017)
Infertility is a problem experienced by some women and men around the world. Most infertility problems in women is caused by impaired reproductive organs or disrupted ovulation.. One factor that causes impaired oocyte maturation is wireless fidelity (Wi-Fi) radiation which has a radio frequency field of 2.45 GHz. The radiation may increase the activity of free radical cells through the fenton reaction pathways that cause infertility because of the disrupted oocyte development. This study aimed to determine the effect of Wi-Fi radiation on the number of oocytes. This was an experimental study using control group design. The subjects were 32 female mice selected through complete random sampling and divided into two groups: control (R0) and exposure (R1). Each group consisted of 16 mice. The Wi-Fi radio frequency used was 2.5 GHz. Mice (R1) were placed closer to Wi-Fi source (± 15cm), and there were two types of laptop PCs and 3G mobile phones connected to internet placed next to mice for 15 hours/28 days. The mice underwent a simultaneous cycle with intraperitoneal injection of PMSG and HCG. Furthermore, the mice were mated with vasectomized male monomatingly to induce ovulation. The fertilization pouch in both oviducts were observed for oocyte collection. The number of oocytes was calculated using an inverted microscope. There was a difference in the number of oocytes between control and exposure group. Statistical tests were analyzed using Mann Whitney U and resulted in significant values (p value = 0.00). No oocytes count in exposure group. In other words, the group underwent anovulation. In conclusion, Wi-Fi radiation affected the number of oocyte stimulation in mice. Therefore, it was important to minimize the risk factors that trigger electromagnetic radiation on reproductive health.